Perundungan Siber melalui Media Sosial Facebook sebagai Faktor Pemicu Percobaan Bunuh Diri - Wisnu Nugroho Hidayat; Chazizah Gusnita (Anomie, 2019)
This time, social media cannot be separate from human life. There is no day without social media especially for teenager who are almost twenty four hours active on social media. Social media such as facebook has become a place for teenangers to do social interaction. The lack of control over the use of social media can have a bad impact for teenager who use it. One of the bad thing that can arise is cyberbullying. The meaning of cyberbullying is a bullying that carried out through online media such a social media. Cyberbullying give the psychological impact for victim that can make depression so that they think and try to commit suicide attempts. The method used in this study is a qualitative approach. The informants of this study are victim of cyberbullying on facebook and has committed suicide attempts.